(untitled) (KIUT Publication, 2025)
In a healthy lifestyle, healthy eating does not mean consuming large amounts of food at once, but rather considering the nutritional value of the food. It is important that the food contains sufficient minerals, proteins, and fats. Each nutrient affects the negative or positive development of the student. Excessive consumption of fats and carbohydrates leads to weight gain.